Acute cardiopulmonary, metabolic, and neuromuscular responses to severe-intensity intermittent exercises - Lisboa, F. D.; Raimundo, J. A. G.; Salvador, A. F.; Pereira, K. L.; Turnes, T.; Diefenthaeler, F.; de Oliveira, M. F. M.; Caputo, F. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to compare cardiopulmonary, neuromuscular, and metabolic responses to severe-intensity intermittent exercises with variable or constant work rate (CWR). Eleven cyclists (28 ± 5 years; 74 ± 7 kg; 175 ± 5 cm; 63 ± 4 ml/kg/min) performed the following tests until exhaustion on separate days: (a) an incremental test; (b) in random order, 2 CWR tests at 95 and 110% of the peak power for the determination of critical power (CP); (c) 2-4 tests for the determination of the highest power that still permits the achievement of maximal oxygen uptake (PHIGH); and (d) 2 random severe-intensity intermittent exercises. The last 2 sessions consisted of a CWR exercise performed at PHIGH or a decreasing work rate (DWR) exercise from PHIGH until 105% of CP. Compared with CWR, DWR presented higher time to exhaustion (635 ± 223 vs. 274 ± 65 seconds), time spent above 95% of VO2max (t95% VO2max) (323 ± 227 vs. 98 ± 65 seconds), and O2 consumed (0.97 ± 0.41 vs. 0.41 ± 0.11 L). Electromyography amplitude (root mean square [RMS]) decreased for DWR but increased for CWR during each repetition. However, RMS and VO2 divided by power output (RMS/PO and VO2/PO ratio) increased in every repetition for both protocols, but to a higher extent and slope for DWR. These findings suggest that the higher RMS/PO and VO2/PO ratio in association with the longer exercise duration seemed to have been responsible for the higher t95% VO2max observed during severe DWR exercise.